Studi pada Pengendalian Mutu Pendidikan Agama Islam di SMAN 1 Labuhan Haji Lombok Timur - Nasri Nasri (Pendidikan Agama Islam STIT Palapa Nusantara, 2019)
None component of success in the world of education is the presence of teaching staff called teachers. The formation of religious values ​​or religusitas is highly prioritized to increase the moral values ​​and attitudes of students. So that the strategy to control the quality of Islamic education can be seen in the class control process developed by the quality development team. School accountability is required to have accountability both to the community and the government. This is a combination of commitment to the standards of success and expectations or demands of parents and the community. This accountability aims to ensure that public funds in supporting educational activities can be used in accordance with predetermined policies in order to improve the quality of education and if possible to provide information about what has been done. For that the school must provide accountability reports and communicate it to parents and the government, and carry out a comprehensive review of the implementation of the school's priority programs in Quality improvement. Islamic religious education is a structured effort to form human beings who have character in accordance with the consequences as a Muslim.